Социокультурная легитимность предпринимательства в украинском обществе первого десятилетия трансформаций - Коржов, Г. (Социология: теория, методы, маркетинг, 2005)
There are analyzed the social and cultural legitimacy level and essence of entrepreneurship in Ukrainian society. Basing on historical and sociological polling data, the author characterizes the main factors which determined such a low level and ambivalent nature of entrepreneurship legitimacy in Ukraine.